Effective Disclosures in Financial Decisionmaking - Hung, Angela A. (RAND Corporation, 2015)
In the financial services market, financial service providers often have better information about the quality, features, fees, risks, and benefits of their products or services than consumers. In this report, we review the literature on consumer disclosures in the financial industry. The primary focus is on disclosures of conflicts of interest, but we also examine use of disclosure associated with other common financial products or services.